2017
DOI: 10.1155/2017/8137627
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Hepatoprotective Effects of Geranium koreanum Methanolic Extract via Downregulation of MAPK/Caspase‐3 Pathway

Abstract: Geranium koreanum (GK) is an indigenous Chinese herbal medicine widely used for the treatment of various inflammation and liver disorders. However, the exact mechanism of action of GK remains unknown. This study aimed to investigate the protective effect and related molecular mechanism of GK on NaAsO2-induced cytotoxicity in HepG2 cells and liver damage in mice. The cytoprotective role of GK was assessed on HepG2 cells using MTT assay. Oxidative stress and lactate dehydrogenase levels were measured with ROS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…All these results, demonstrate a non-cytotoxic and antiinflammatory effects on LPS-induced Raw 264.7 cells. The toxic effects of gastric acid and stomach contents lead to epithelial injury and cell death in esophageal mucosa [1,23]. To evaluated protective effects of geraniin on reflux esophagitis rats, experimental rats were orally administrated with geraniin (15 and 30 mg/ kg body weight) and H2 inhibitor ranitidine 30 mg/kg body weight as positive control.…”
Section: Discussionmentioning
confidence: 99%
“…All these results, demonstrate a non-cytotoxic and antiinflammatory effects on LPS-induced Raw 264.7 cells. The toxic effects of gastric acid and stomach contents lead to epithelial injury and cell death in esophageal mucosa [1,23]. To evaluated protective effects of geraniin on reflux esophagitis rats, experimental rats were orally administrated with geraniin (15 and 30 mg/ kg body weight) and H2 inhibitor ranitidine 30 mg/kg body weight as positive control.…”
Section: Discussionmentioning
confidence: 99%
“…2E ), which suggested that the 90-day oral administration of OMT, MT and OMT + MT had no obvious effect on the normal growth of mice. Serum biochemistry serves as an important indicator of physiological abnormalities in liver intoxication ( 22 ). The values of biochemical indicators following 90 days of exposure to OMT, MT and OMT + MT are presented in Table I .…”
Section: Resultsmentioning
confidence: 99%
“…The increased release of liver enzymes, including ALT, AST and LDH, as well as TBiL, is recognized as an initial indicator of physiological dysfunction and liver toxicity ( 22 , 28 ). However, hepatic histopathological evaluation is currently the standard method for determining the degree of liver injury during exposure to xenobiotics ( 29 ).…”
Section: Discussionmentioning
confidence: 99%